Biofilm Formation of Pseudomonas geniculata (Wright, 1895) Chester, 1901 on Three Fungals Species: Relationship with Incubation Time and Fungal Diameter Size - Siradje, Andi Lindhemuthianingrum; D. Prijambada, Irfan; Retnaningrum, Endah (KnE Life Sciences, 2017)
Pseudomonas geniculata has been isolated from uncontaminated vertisol in Kulon Progo district. The isolate is hydrocarbonoclastic bacterium capable of forming biofilm on the fungal hyphae. Sinergy of both microbe in the form fungal-bacteria biofilm produce high ability to degrading hydrocarbon and survive in its pollution environment. The purpose of this research was to evaluate ability of Pseudomonas geniculata (Wright, 1895) Chester, 1901 to form biofilm and its attachment on three fungals species such as Penicillium sp., Penicillium funiculosum and Penicillium crustosum. The diameter size of fungal hyphae was of 1.3 µm, 1.9 µm and 2.4 µm, respectively. P. geniculata required at least 48 h to form biofilms on Penicillium sp. hyphae when incubated in mineral Bushnell Haas Medium suplemented with 2 % glucose at room temperature, with maximal biofilm formation being evident at 360 h. Biofilm attachment on Penicillium sp. hyphae was disrupted by the vortex power of 5 rpm for 20 s. Interaction of P. geniculata and Penicillium sp. that has a smallest diameter size of hypha were more successful on biofilm formation and attachment which could contribute to bacterial survival in environmental stresses. Keyword: Biofilm, fungal hyphae, Pseudomonas geniculata (Wright, 1895) Chester, 1901, Penicillium.